2020
DOI: 10.3389/fneur.2020.00851
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity in Multiple Sclerosis

Abstract: Comorbidities in patients with multiple sclerosis (MS) has become an area of increasing interest in the recent years. A comorbidity is defined as any additional disease that coexists in an individual with a given index disease and that is not an obvious complication of the index disease. The aim of this review is to describe the current evidence regarding the range of comorbidities in the population with MS reported in different countries and the current knowledge about the influence of comorbidities on the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
96
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 105 publications
4
96
0
5
Order By: Relevance
“…For a complex disease like MS, individual drugs have proven to be ineffective for management and treatment and have failed to inhibit MS progression. A multimodal approach may be more effective at addressing complex chronic diseases, including MS and its comorbidities [ 123 ]. Administering a pro-remyelinating drug may not be as efficacious for long-term use without reducing recurring chronic inflammation.…”
Section: The Evidence Speaks: Multifactorial Diseases Must Be Trementioning
confidence: 99%
See 1 more Smart Citation
“…For a complex disease like MS, individual drugs have proven to be ineffective for management and treatment and have failed to inhibit MS progression. A multimodal approach may be more effective at addressing complex chronic diseases, including MS and its comorbidities [ 123 ]. Administering a pro-remyelinating drug may not be as efficacious for long-term use without reducing recurring chronic inflammation.…”
Section: The Evidence Speaks: Multifactorial Diseases Must Be Trementioning
confidence: 99%
“…It is likely that microbiota composition plays an influential role in MS pathogenesis. Correcting intestinal dysbiosis may also improve cognitive behaviour and depression [ 127 ], which is a common symptom of MS [ 123 , 128 ]. Therefore, future treatments should consider how disease-modifying treatments (DMTs) can be combined with therapies targeted at the microbiota.…”
Section: The Evidence Speaks: Multifactorial Diseases Must Be Trementioning
confidence: 99%
“…It is likely that microbiota composition plays an influential role in MS pathogenesis. Correcting intestinal dysbiosis may also improve cognitive behaviour and depression [127], which is a common symptom of MS [123,128]. Therefore, future treatments should consider how disease-modifying treatments (DMTs) can be combined with therapies targeted at the microbiota.…”
Section: The Evidence Speaks: Multifactorial Diseases Must Be Treatedmentioning
confidence: 99%
“…6,7 30.5% was observed by Boeschoten and 23.7% by Magyari et al in their systematic review studies. 8,9 Saba Karimi et al reported 47.1% in 87 patients in a cross sectional study. 10 Kessler et al, Kovacs et al and Simpson et al reported that the incidence in women gender are more vulnerable when compared to men at the time of first episode.…”
Section: Introductionmentioning
confidence: 98%